DYNAMIC MUSCULAR ENDURANCE IN CONNECTION WITH THE STATE OF PSYCHOPHYSIOLOGICAL FUNCTIONS OF QUALIFIED FEMALE ATHLETES - FEDORCHUK, S.; PETRUSHEVSKYI, Ye. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
The aim of the study was to determine the relationship between dynamic muscular endurance of the hand (according to the tapping test) with the state of psychophysiological functions of qualified female handball players at different stages of sports training. Diagnostic complex "Diagnostics-1" (MV Makarenko, VS Lyzogub) was used to determine the state of psychophysiological functions of athletes, the maximum rate of movement of the brush. Dynamic muscular endurance of the right and left brushs, properties of the nervous system (functional mobility and strength of nervous processes), the effectiveness of sensorimotor activity and the dynamics of nervous processes, the latency period of a complex reaction of choice, the accuracy of the reaction to a moving object were studied in accordance with the purpose of the study. Dynamic muscular endurance of subdominant hand was significantly higher in older female athletes. There is a tendency to increase the dynamic muscular endurance of the dominant hand in older female athletes. The asymmetry according to the indicators of the tapping test between the right and left hand was lower in the older age group than in the younger age group. In general, the results indicate a higher level of dynamic muscular endurance of both arms in older female athletes, who are more adapted to long-term specific physical activity. That is, the improvement of special training in handball leads to the development of dynamic muscular endurance. This is confirmed by the results of the correlation analysis of the obtained data: dynamic muscular endurance of the subdominant arm was associated with the experience of sports training. The maximum rate of movement of the brush of both hands in the surveyed female athletes was associated with the strength of nervous processes and the accuracy of the reaction to a moving object. The dynamic muscular endurance of the dominant hand' brush was associated with the functional mobility of nervous processes.
Keywords: dynamic muscular endurance, tapping test, state of psychophysiological functions, highly qualified female athletes, handball